Lactobacillus GG and other probiotics in pediatric food allergy treatment: a network meta-analysis - Li Xiaohua; Du Yiting; Li Qin; Zhai Yang; Wu Shumao; Peng Li; Pan Yi; Chen Lingmei; Liao Wenge; Li Maoxia (Frontiers in Nutrition)
BackgroundFood allergies are a significant health challenge in children, impacting quality of life and posing a burden on healthcare systems. Probiotics have been proposed as a potential treatment for food allergies, but their efficacy remains controversial. This systematic review and network meta-analysis aimed to assess the comparative effectiveness of different probiotics in managing pediatric food allergies.MethodsFollowing the Cochrane Handbook and PRISMA guidelines, a systematic search was conducted across PubMed, Cochrane Library, Web of Science, and Medline up to March 5, 2024. Randomized controlled trials (RCTs) evaluating probiotics for pediatric food allergies were included. The Cochrane risk of bias tool was used for quality assessment. Network meta-analyses were performed using random-effects models to calculate standardized mean differences (SMDs), odds ratios (ORs), and surface under the cumulative ranking curve (SUCRA) for different probiotics.ResultsSixteen RCTs involving 1,502 participants aged 1 month to 10 years were included. Eight probiotic interventions were analyzed. Lactobacillus GG (LGG) was identified as the most effective in reducing Scoring Atopic Dermatitis (SCORAD) scores (SMD = −4.24, 95% CI [−7.12, −1.36]; p < 0.05) and improving quality of life. For IgE regulation, Lactobacillus acidophilus (LB) demonstrated the greatest efficacy (p < 0.05). Publication bias was minimal for SCORAD and IgE outcomes, but some bias was detected for quality of life due to the limited number of studies.ConclusionThis study suggests that LGG is the most effective probiotic for improving clinical outcomes in pediatric food allergy management, particularly for SCORAD scores and quality of life. However, further high-quality RCTs are needed to validate these findings and explore the mechanisms underlying the differential efficacy of probiotic strains.